Pengaruh Profitabilitas, Likuiditas dan Kepemilikan Manajerial terhadap Nilai Perusahaan - Citra Nur utami; Listyorini Wahyu Widati (Owner : Riset dan Jurnal Akuntansi, 2022)
Company value is a condition of achievement in a company that has earned public trust. Firm value is an important indicator in observing shareholder prosperity. There are various factors that can affect the value of the company. The purpose of this study was to determine and examine the effect of profitability, liquidity, and managerial ownership on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This research is a quantitative research with the object of research in the form of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020 as many as 686 companies. While the selected sample is 329 data on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2020. The sample in this study was taken using a purposive sampling technique. The type of data used in this research is secondary data. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that liquidity as measured by Current Ratio (CR) has a significant negative effect on firm value, while managerial ownership as measured by MOWN has a significant positive effect on firm value. However, profitability as measured using Ratio on Assets (ROA) has no effect on firm value. Keywords: firm value; profitabilit; liquidity; managerial ownership